2007
DOI: 10.1177/0165551506076392
|View full text |Cite
|
Sign up to set email alerts
|

Lost in translation: contributions of editors to the meanings of text

Abstract: Background. Authors of scientific articles in one language are often required to provide abstracts of their papers in a second language, and they use a variety of ways to achieve this. Aims. The aims of our studies were (i) to assess the effects of using native English speakers to improve non-native speakers' translations of their abstracts, and (ii) to explore the variations in edits produced by different native speakers. Methods. In Study 1, a French abstract was translated into English by two French authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In contrast, language and writing features are more likely to be judged subjectively because gatekeepers' expertise in this dimension varies widely. The latter is probably influenced by individual characteristics such as the reader's native language and culture, and personal preference for language and writing style [ 8 ]. As a result, feedback about the language and writing may be less likely to help authors improve their manuscripts than feedback about the specialized content.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, language and writing features are more likely to be judged subjectively because gatekeepers' expertise in this dimension varies widely. The latter is probably influenced by individual characteristics such as the reader's native language and culture, and personal preference for language and writing style [ 8 ]. As a result, feedback about the language and writing may be less likely to help authors improve their manuscripts than feedback about the specialized content.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, these nine scales had loaded on three components or factors, and in the present study, we chose to use two from each factor; however, the three factors reported by Hartley et al (2007) did not emerge. Principal Components Analyses and Varimax Rotations with Kaiser normalization (Tabachnick & Fidell, 2001) showed that the scores on the first four subscales loaded on a single factor in all three studies, but that the scores on Subscales 5 and 6 either loaded on another factor (Studies 1 and 2) or another two factors (Study 3).…”
Section: Methodsmentioning
confidence: 97%
“…The six subscales used in this inquiry were chosen from nine scales initially used by Hartley, Branthwaite, Ganier, and Heurley (2007). In their study, these nine scales had loaded on three components or factors, and in the present study, we chose to use two from each factor; however, the three factors reported by Hartley et al (2007) did not emerge.…”
Section: Methodsmentioning
confidence: 99%
“…A study of abstracts written in French, translated into English by two French authors and then edited by two English native speakers found the editors imposed their own styles of writing and changed the original meaning in different ways. Furthermore readers recognized the abstracts as having different voices [13].…”
Section: Assistance From Author's Editors and Translatorsmentioning
confidence: 99%